Nitrogen management improves lodging resistance and production in maize (Zea mays L.) at a high plant density - Irshad AHMAD; Maksat BATYRBEK; Khushnuma IKRAM; Shakeel AHMAD; Muhammad KAMRAN; Misbah; Raham Sher KHAN; Fu-jiang HOU; Qing-fang HAN (Journal of Integrative Agriculture, 2023)
Lodging in maize leads to yield losses worldwide. In this study, we determined the effects of traditional and optimized nitrogen management strategies on culm morphological characteristics, culm mechanical strength, lignin content, root growth, lodging percentage and production in maize at a high plant density. We compared a traditional nitrogen (N) application rate of 300 kg ha−1 (R) and an optimized N application rate of 225 kg ha−1 (O) under four N application modes: 50% of N applied at sowing and 50% at the 10th-leaf stage (N1); 100% of N applied at sowing (N2); 40% of N applied at sowing, 40% at the 10th-leaf stage and 20% at tasseling stage (N3); and 30% of N applied at sowing, 30% at the 10th-leaf stage, 20% at the tasseling stage, and 20% at the silking stage (N4). The optimized N rate (225 kg ha−1) significantly reduced internode lengths, plant height, ear height, center of gravity height and lodging percentage. The optimized N rate significantly increased internode diameters, filling degrees, culm mechanical strength, root growth and lignin content. The application of N in four split doses (N4) significantly improved culm morphological characteristics, culm mechanical strength, lignin content, and root growth, while it reduced internode lengths, plant height, ear height, center of gravity height and lodging percentage. Internode diameters, filling degrees, culm mechanical strength, lignin content, number and diameter of brace roots, root volume, root dry weight, bleeding safe and grain yield were significantly negatively correlated with plant height, ear height, center of gravity height, internode lengths and lodging percentage. In conclusion, treatment ON4 significantly reduced the lodging percentage by improving the culm morphological characteristics, culm mechanical strength, lignin content, and root growth, so it improved the production of the maize crop at a high plant density.